(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
حضرت عينات من الألومينا المحملة بأيونات الكبريتات و الموليبدينيوم بنسب مختلفة بطريقة النقع. عولجت العينات المحضرة عند درجة حرارة 550°C لمدة 6 ساعات . يؤدي تحميل الكبريتات و الموليبدينيوم إلى تناقص المساحة السطحية النوعية للألومينا ويكون التناقص أكبر في حالة الموليبدينيوم. تؤدي عملية التحميل إلى تناقص حجم المسام الكلي و ازدياد نصف قطر المسام الوسطي. بين طيف الأشعة السينية XRD أن وجود الكبريتات و الموليبدينيوم لا يغير في البنية البلورية للألومينا . كما بين طيف الأشعة تحت الحمراء FTIR وجود ارتباط بين الكبريتات و الموليبدينيوم مع سطح الألومينا. يتناقص الفاقد الوزني للألومينا عند التحميل بالكبريتات و الموليبدينيوم, وتتفكك الكبريتات عند الدرجة 700°C بينما يتفكك أوكسيد الموليبدينيوم عند الدرجة 800°C كما يظهر من دراسات التحليل الوزني التفاضلي TG-DTA . Some samples of alumina supporting with sulfate ions and molybdenium were prepared by impregnation method. Supported samples were calcinated at 550°C for 6h. Presence of sulfate ions and molybdenium lead to decreasing of the specific surface area of alumina, and in the ease of molybdenium the decreasing value was higher. The total pore volume was decreased with the pore size was increased. XRD patterns showed that the incorporation of sulfate ions and molybdenium did not affect crystalin structure of alumina. FTIR spectra showed the bonding between sulfate ionsmolybdenium and alumina. The TG-DTA studies showed that the losses mass was decreased when the sulfate ions and molybdenium were incorporated, sulfate ions and molybdenium oxide decomposed at 700°C and 800°C respectively .